Clinical characteristics of vulnerable populations hospitalized and diagnosed with COVID-19 in Buenos Aires, Argentina - Yacobitti, A. (2021)
There is not in Argentina publications regarding the presentation of patients with COVID-19 requiring hospitalized and emergency care in vulnerable populations (lower incomes and less education tend at greater risk for poor health status and healthcare access), and it has few reports in developing countries. The objective is to determine whether in the care of vulnerable patients, to succeed against COVID-19, multiple public health tools and interventions will be needed to minimize morbidity and mortality. The study is a prospective cohort investigation of patients with lab-confirmed COVID-19, who required to any of the Health Centers response from April 8, 2020, to August 18, 2020. In Buenos Aires Metropolitan Area (AMBA), April 8, 2020 the virus was identified in patients hospitalized in the "Southeast Network" (SN), AMBA. SN covering an area of 661 square kilometers, with 1.8 million inhabitants residing in urban, and rural areas. A total of 14 health centers with different levels of care complexity provide care to patients in the region. The information of each patient with COVID-19 evaluated by SN, was incorporated in an Epidemiological Dashboard. The investigation was designed and reported with consideration of observational studies in epidemiology. We describe the hospitals presentation and care of persons who required SN response and were ultimately diagnosed with COVID-19. From April 8, 2020, to August 18, 2020, were included 1495 patients with lab-confirmed COVID-19 in SN. A total of 58% patients were men, and the mean age (SD) was 48.9 (15.59) years. Eighty one percent patients with pre-existing diseases, most frequent hypertension and diabetes, but hypertension, chronic lung disease, and cardiovascular disease presented higher risk. A total of 13% were hospitalized in Intensive Therapy Unit. The mortality of the cohort was 9.77%. Mortality was higher for patients aged 65 or more (OR 5.09), and for those had some pre-existing disease (OR 2.61). Our observations are consistent with reports demonstrating older persons, and those with comorbidities have the highest risk of mortality related to COVID-19. However, unlike other reports from developed or some developing countries, the mortality in our study is lower. This finding may be related to age of our cohort is younger than other published. Also, the health system was able to respond to the demand.